Legal Protection For Children Born as A Result of Rape Victimization - Erma Hari Alijana; Muhammad Mustofa; Fauzie Yusuf Hasibuan (Pelopor Publikasi Akademika, 2025)
This study aims to analyze the legal protections for children born as a result of rape in Indonesia, focusing on the gaps in the current legal system and the challenges these children face in accessing their rights. The research uses a normative juridical method combined with qualitative analysis to examine existing laws and regulations related to child protection, with a particular focus on the legal status of children born from rape. The findings reveal that while Indonesia has child protection laws in place, there are significant gaps in the application of these laws for children born as a result of rape, leaving them vulnerable to discrimination and a lack of legal clarity regarding their rights. The study concludes that there is an urgent need for legal reforms to ensure that these children are provided with the same legal protections and rights as other children, including access to healthcare, education, and protection from further harm. It is essential to strengthen legal frameworks and ensure consistent application of child protection laws to guarantee the rights and welfare of all children, regardless of their birth circumstances.